2001
DOI: 10.4319/lo.2001.46.7.1814
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of selenium on mercury assimilation by fish populations near Sudbury metal smelters?

Abstract: Abstract-In this study, the concentrations of Se and Hg were determined in perch (Perca flavescens) and walleye (Stizosedion vitreum) muscle from nine lakes that varied in distance (4-204 km) from the metal smelters of Sudbury, Canada. Significant inverse relationships between Se and Hg in perch (r 2 ϭ 0.79, P Ͻ 0.05) and walleye tissue (r 2 ϭ 0.97, P Ͻ 0.01) were detected, which suggests a strong antagonistic effect of Se on Hg assimilation by these fish species. Concentration of Hg decreased exponentially wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 16 publications
4
67
0
Order By: Relevance
“…Southworth et al (2000) observed a long-term increase in mercury concentrations in the largemouth bass following the reduction of waterborne selenium. Chen et al (2001) further found a significantly negative correlation between the mercury concentrations in perch and walleye muscles and selenium concentrations. The mechanism of interaction between these two elements in the bioassimilation processes has not yet been clarified although it appears to be related to the element competition between mercury and selenium in fish muscles.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Southworth et al (2000) observed a long-term increase in mercury concentrations in the largemouth bass following the reduction of waterborne selenium. Chen et al (2001) further found a significantly negative correlation between the mercury concentrations in perch and walleye muscles and selenium concentrations. The mechanism of interaction between these two elements in the bioassimilation processes has not yet been clarified although it appears to be related to the element competition between mercury and selenium in fish muscles.…”
Section: Resultsmentioning
confidence: 78%
“…Culvin-Aralar & Furness 1991). However, field studies on the Se-Hg interaction in freshwater fish are relatively scarce, and the data collected from these are often controversial (Chen et al 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se maintained a molar excess over Hg in all species examined in this study, with Se concentrations never reaching those considered to be a toxic threat (Lemly 1996). Exceptionally large Se molar advantages have been recorded through lower trophic groups (Chen et al 2001;Belzile et al 2006, Karimi et al 2013), but these molar advantages tend to decrease up the food chain to higher organisms (Yang et al 2008;Kehrig et al 2009;Fang et al 2011). This relationship was also evident in the present study, with the reduced molar advantage with increasing trophic level being the result of the biomagnification of Hg across trophic levels, as Se concentrations showed either no biomagnification or weak reductions with increasing d 15 N. The stability of the Se concentrations across the food web may be the result of a metabolic balancing act in which Se molar advantage over Hg is offset against maintaining Se concentrations at a level that does not cause toxicity problems (Lemly 1996).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies suggest an important role of Se in the reducing bioaccumulation of Hg in fish (50)(51)(52) and inverse relationships between fish tissue Hg and the abundance of Se present in the ecosystem have been noted (53,54). Selenium supplementation of lake waters in Sweden resulted in a 75%-85% reduction in Hg levels of fish over a 3-year period (55) and loss of Se can have the opposite effect.…”
Section: How Does Selenium Inhibit Hg-bioaccumulation In Fish?mentioning
confidence: 99%